KADARKUM: The legal awareness program for enhancing citizen engagement in supporting rural development - Satrio Alpen Pradanna; Hendri Irawan; Nur Fajriani S; Prayoga Bestari (Goodwood Publishing, 2024)
Purpose: This study aimed to assess the role of the KADARKUM program in enhancing citizens’ legal awareness to support rural development. Research Methodology: This study uses a qualitative approach and employs a literature review method to analyze the existing literature related to legal awareness improvement and citizen engagement in village development. It involves an in-depth review of the relevant literature to understand the factors influencing legal awareness among rural communities, effective strategies for enhancing legal awareness, and the benefits of citizen engagement in promoting rural development. Results: The findings indicate that enhancing legal awareness through the KADARKUM programme has the potential to increase citizen engagement in supporting rural development. Limitations: This study was limited to a literature review and did not include original data collection or empirical research in a specific location. Contributions: This study provides valuable insights into the significance of improving legal awareness as a foundational step in fostering citizen engagement to support rural development. The implications of this study can be used to formulate effective policies and intervention programs for community development. Novelty: The novelty of this study lies in its focus on the KADARKUM programme as a potential mechanism to strengthen legal awareness and citizen engagement in the context of rural development.